Correlation between work-related musculoskeletal wrist pain and level of disability among health practitioners - Syeda Nida Fatima, Arooj Hanif, Ayesha Noureen, Fatima Ijaz, Sobia Ghafoor, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Wrist pain is not only a common but a chronic condition among individuals. Professionals’ required repetitive movements of wrist and hand were at high risk of developing this condition which ultimately affects their functional and work related activities. Aim: To find a correlation between work-related musculoskeletal wrist pain and level of disability among health practitioners. Methods: Total 227 participants were included in this cross-sectional survey sample size was calculated using epi.tools.com data was collected using convenient sampling at Jinnah Hospital, Social Security Hospital of Lahore, Services Hospital, Pakistan. Patient Rated Wrist Evaluation questionnaire was used for evaluations which consist of 15 questions regarding pain and functional disability level ranging 0 to 10 this questionnaire had excellent validity and reliability. Results: Results reported strong correlation between wrist pain and level of disability (p<0.05). Level of disability in doing work (job or everyday work) was 53(23.3%) participants had no disability, 103(45.4%) had mild disability, 66(29%) had moderate disability and 5(2.2) had sever disability. Total disability level was reported as out of 227 participants 101(44.5%) participants reported no disability, 103(45.4%) had mild disability and 23(10.1%) had moderate disability the overall disability level estimated was 55%. Conclusion: This study concluded that strong correlation between musculoskeletal wrist pain related to work among health practitioners and level of disability due to pain was reported as mild to moderate.